Knowledge and Interest: Exploring Households’ Participation in School-based TASAF Development Projects in Morogoro Rural District - Kinemo, Stella Malangalila (Journal of Policy and Leadership, 2018)
This study assessed households’ participation in the education sub-project co-ordinated by Tanzania Social Action Fund (TASAF) in Morogoro Rural District. Specifically it engaged to measure the levels of households’ participation via the use of two typological attributes, namely: knowledge and interests of the household actors in the construction of primary school classrooms. The article is a result of a study that utilized both qualitative and quantitative data from a sample size of 72 households drawn from three villages of Lukulunge, Mbwade and Dakawa Ukutu. Both, structured interview guides were used to collect data from key informants and structured questionnaires were administered to household actors. Data were analysed through the use of descriptive Statistics to assess the levels of households’ participation in the attendance of TASAF meetings, contribution of cash, contribution of labour, and involvement in decision making. Results categorises four typological groups of actors with various level of households’ participation in TASAF project namely: Dormant Elites, Apathy to TASAF, TASAF Victors, and TASAF Victims as well. However, of all categories, TASAF Victims dominated in the areas, and consequently the study revealed poor levels of households’ participation in this TASAF sub-project. The study explains several reasons that account for this and offers recommendations.